HUBUNGAN SIKAP TENTANG METODE KONTRASEPSI DENGAN PERILAKU PEMILIHAN METODE KONTRASEPSI PADA AKSEPTOR KONTRASEPSI WANITA - Lasiah Susanti; Echa Putri Ayu Rimadhona MZ (LPPM Universitas Abdurrab, 2023)
Family Planning Program (KB) is one of the efforts made by the government to reduce the high child birth and maternal mortality rates. This program has been implemented in Indonesia since June 29th, 1970 along with the formation of the National Family Planning Coordinating Board (BKKBN). Riau Province is among the 8th lowest active KB users among 34 provinces in Indonesia. Of the various contraceptive methods available, the use of non-long-term contraceptive methods (non-MKJP) namely injections and pills is a method of contraception that is widely used in Indonesia, especially in Pekanbaru. The rate of use of the Long-Term Contraception Method (MKJP) in Indonesia especially Pekanbaru City is still lower compared to non-MKJP. This is due to the lack of public knowledge about the advantages of the MKJP method, so that a person could not determine its attitude or behavior in the selection of contraception that must be used. To find out the correlation of attitude about contraception method with behavior of choosing contraception method in female contraception acceptors in the pekanbaru city health center. The study was conducted by observational analytic method, with a cross sectional study design. This research was conducted at 12 health centers in the city of Pekanbaru. The sampling technique is done by stratified random sampling with a large sample of 400 respondents. Statistical test results using Pearson comparison test. There is a correlation (p-value = 0,000) and showed a significant relationship (p-value <0.05) between attitudes about contraceptive methods and the behavior of choosing contraceptive methods in female contraceptive acceptors in Pekanbaru City Health Center.